Evaluation of the lower limb vasculature before free fibula flap transfer. A prospective blinded comparison between magnetic resonance angiography and digital subtraction angiography. Issue 7 (27th August 2013) - Klein, Steven; Van Lienden, Krijn P.; Van't Veer, Marcel; Smit, Jeroen M.; Werker, Paul M.N.
<x xml:space="preserve">Abstract</x> Introduction The aim of this study was to compare magnetic resonance angiography (MRA) with digital subtraction angiography (DSA) in the preoperative assessment of crural arteries and their skin perforators prior to free fibular transfer. Patients and methods Fifteen consecutive patients, scheduled for free vascularized fibular flap transfer, were subjected to DSA as well as MRA of the crural arteries of both legs (n = 30). All DSA and MRA images were assessed randomly, blindly, and independently by two radiologists. Each of the assessors scored the degree of stenosis of various segments on a 5 point scale from 0 (occlusive) to 4 (no stenosis). The Cohen's Kappa coefficient was used to assess the agreement between DSA and MRA scores. In addition, the number of cutaneous perforators were scored and the assessors were asked if they would advise against fibula harvest and transplantation based on the images. Results A Cohen's Kappa of 0.64, indicating "substantial agreement of stenosis severity scores" was found between the two imaging techniques. The sensitivity of MRA to detect a stenosis compared with DSA was 79% (CI95%:60–91), and a specificity of 98% (CI95%: 97–99). In 53 out of 60 assessments, advice on suitability for transfer were equal between DSA and MRA. The median number of cutaneous perforators that perfuse the skin overlying the fibula per leg was one for DSA as well as MRA (P = 0.142).Conclusions A substantial agreement in the assessment of stenosis severity was found between DSA and MRA. The results suggest that MRA is a good alternative to DSA in the preoperative planning of free fibula flap transplantation. © 2013 Wiley Periodicals, Inc. Microsurgery 33:539–544, 2013.